2018
DOI: 10.26773/mjssm.180910
|View full text |Cite
|
Sign up to set email alerts
|

The Brain and Movement: How Physical Activity Affects the Brain

Abstract: In recent years, many studies have demonstrated the importance of movement for the human body, from the improvement of cardiovascular effi cacy to the enhancement of muscular functions, metabolic balance, and organ systems. Th e brain is no exception and benefi ts greatly from movement, both structurally and functionally. Memory, creativity, and intelligence, are only a few of the many things that are regulated by the brain. Th e literature demonstrates the benefi ts of physical activity on numerous factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
2
23
0
4
Order By: Relevance
“…The psychophysiological effects of music have been widely investigated in both psychology (De Giorgio et al, 2017;Benke et al, 2018;Innes et al, 2018;Padovan et al, 2018) and in exercise and sport related fields (Jarraya et al, 2012;Terry et al, 2012). The effects of exercise on the brain are well known (for a review see De Giorgio, 2017, De Giorgio et al, 2018a, but the effect that music has on exercise and its cerebral counterpart has only recently been investigated (Bigliassi et al, 2017;Tabei et al, 2017). It has been demonstrated that music is able to trigger behavioral changes, i.e., there is an underlying modification of brain function which can induce people to increase their exercise adherence and participation (Altenmüller and Schlaug, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The psychophysiological effects of music have been widely investigated in both psychology (De Giorgio et al, 2017;Benke et al, 2018;Innes et al, 2018;Padovan et al, 2018) and in exercise and sport related fields (Jarraya et al, 2012;Terry et al, 2012). The effects of exercise on the brain are well known (for a review see De Giorgio, 2017, De Giorgio et al, 2018a, but the effect that music has on exercise and its cerebral counterpart has only recently been investigated (Bigliassi et al, 2017;Tabei et al, 2017). It has been demonstrated that music is able to trigger behavioral changes, i.e., there is an underlying modification of brain function which can induce people to increase their exercise adherence and participation (Altenmüller and Schlaug, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To ganglia (9) and the cerebellum (6), and each structure affects the other (8,10). These structures organize the motor response and are very sensitive to training (26), which shows a long-lasting positive effect of sport training through sensorimotor adaptations (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…Physical education lesson di ers from the usual lessons of emotion, the ability to move. (Castelli, 2007;François & Roy, 2008;Gary et al, 2012;Donnelly et al, 2016;Shuba, 2016;De Giorgio et al, 2018). It is at the lessons of physical culture at school that a whole complex of methodological approaches, recommendations, principles, means and methods of in uence is realized.…”
Section: Discussionmentioning
confidence: 99%
“…e negative consequences of insu cient motor activity are accompanied by a decrease in the resistance of the young organism to colds and infectious diseases, the prerequisites for the formation of a weak, untrained heart are created. Lesson in physical culture at school is an organized form of classes at school (Castelli, 2007;Shuba, 2016;Donnelly et al, 2016;De Giorgio et al, 2018). From primary school age should develop most of the physical abilities of schoolchildren, such as exibility, speed and others.…”
Section: Introductionmentioning
confidence: 99%